Some main aspects of state sovereignty, with special reference to the distinction between external and internal sovereignty - Dolcetti, A (2016)
The problem at the heart of the Thesis can be formulated, in its simplest form, as follows: What is (the nature of) state sovereignty? I approach this problem with a view to deploying one of the methodologies developed by analytical jurisprudence in tackling the quaestio vexata: What is (the nature of) law? In particular, I seek to deploy a method of the sort employed by John Finnis in offering an explanatory definition of law. Accordingly, I focus attention on the characteristic features of the paradigm case of state sovereignty. The trajectory drawn by the six Chapters of the Thesis is impelled by the following research question: what are the standing human needs that make sovereignty (despite the risks associated with its exercise) necessary and desirable for a state, both internally and externally? In order to answer this question, I first consider how external and internal (state) sovereignty have been conceptualised in the context of analytical jurisprudence. This allows me to establish that (state) law and (state) sovereignty are co-related, and directs me toward a study of legal discourse. On the basis of this correlation, I show that the concepts of external and internal sovereignty are associated with a (meta-)claim to state legal independence and a (meta-)claim to state legal supremacy. By analysing those claims, in the context of public international law and constitutional law discourse, I demonstrate that two needs in combination, the need for self-determination and the need for autonomy, underpin those claims. I conclude by arguing that state sovereignty, both externally and internally, is made necessary and desirable (despite the risks associated with its exercise) by the state political community’s standing needs for self-determination and autonomy, which are rooted in the necessity and desirability of protecting a human person’s freedom in practical reasonableness.